2021
DOI: 10.1039/d0md00328j
|View full text |Cite
|
Sign up to set email alerts
|

Chemical modulation of Kv7 potassium channels

Abstract: This review describes the synthetic and medicinal chemistry of small molecule modulators of the voltage-gated Kv7 (KCNQ) potassium channels and the available data of their biological and clinical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 377 publications
0
12
0
Order By: Relevance
“…A great deal of attention has been focused on achieving rescue of Kv7 channel function across the numerous pathogenic variants found in Kv7.2 or Kv7.3 subunits. A number of Kv7 activators have been reported that could provide potential recovery of function in Kv7.2 mutations ( Borgini et al., 2021 ; Incontro et al., 2021 ; Kanyo et al., 2020 ; Larsson et al., 2020b ; Vanoye et al., 2022 ), although non-specific actions or side effects have led to removal of some of these drugs from clinical use ( Brickel et al., 2020 ). The proband with Kv7.2H260del had resolution of seizures through use of CBD:THC oil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A great deal of attention has been focused on achieving rescue of Kv7 channel function across the numerous pathogenic variants found in Kv7.2 or Kv7.3 subunits. A number of Kv7 activators have been reported that could provide potential recovery of function in Kv7.2 mutations ( Borgini et al., 2021 ; Incontro et al., 2021 ; Kanyo et al., 2020 ; Larsson et al., 2020b ; Vanoye et al., 2022 ), although non-specific actions or side effects have led to removal of some of these drugs from clinical use ( Brickel et al., 2020 ). The proband with Kv7.2H260del had resolution of seizures through use of CBD:THC oil.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is possible that CBD could interact with other receptors or channels in tsA-201 cells that could invoke other factors that modulate Kv7 channels (i.e. PiP2, PKC, calmodulin, arachidonic acid, and ERK1-2) ( Borgini et al., 2021 ; Greene and Hoshi, 2016 ; Hudson et al., 2019 ; Larsson et al., 2020a ).…”
Section: Discussionmentioning
confidence: 99%
“…Activated PKC phosphorylates the C-terminus in the calmodulin (CaM) binding site of the Kv7.2 subunit assisted by A-kinase-anchoring protein AKAP79/150. The phosphorylated state of the channel destabilizes the Kv7 channel/PIP 2 complex and consequently PIP 2 hydrolysis suppresses the M-current [80][81][82][83].…”
Section: Discussionmentioning
confidence: 99%
“…The morphological formation of these neurons within the hippocampus leads to the further subfield classification of pyramidal cells in what is known as Cornu Ammonus (CA), divided into CA1, CA2, and CA3 [ 49 , 50 ]. These regions serve an important role in localizing KCNQ channel function in synaptic plasticity [ 49 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. Within synaptic plasticity, two major models involved in the application of neural plasticity are long-term potentiation (LTP) and long-term depression (LTD) [ 59 ].…”
Section: Modulation Of Synaptic Plasticity By Kcnq Channelsmentioning
confidence: 99%
“…This plays a key role in maintaining the K + gradient for channel mechanosensation to carry K + into hair cells to stimulate auditory sensation [ 14 , 38 ]. KCNQ4 mutations are often associated with auditory hearing loss and have therefore been a key target in developing pharmacotherapeutic options for hearing loss [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]. KCNQ5 is most expressed in neural tissue, including the retinal pigment epithelium [ 48 ].…”
Section: Introductionmentioning
confidence: 99%